Evaluation of university employees’ work behaviours performance via entropy based topsis methods - Karakaş, Ayhan; Kıngır, Said; Öztel, Ahmet; Karakaş, Ayhan; Öztel, Ahmet (Elektronik Sosyal Bilimler Dergisi, 2016)
This study is aimed to measure the employees' job performance behavior via the entropy based TOPSIS methods. For this purpose, work behaviors; burnout, emotional labor, intention to leave, and job satisfaction scales are taken as assessment criteria and a questionnaire is applied on public university employees. Integrated evaluation of all criteria is vital for performance measurement. At this point multi-criteria decision-making methods present an appropriate framework. MCDM methods are very suitable decision tools for measuring employee’s performance. This method is used in order to measure performance for not only the number of work but also the attitude according to business, enterprise, and people getting services. Considering the researches done via TOPSIS are few, this work contributes to the literature. Because of appropriate scales are in opposite directions, TOPSIS method accepted as a MCDM method is used to reduce all scales to only one value. As a result, applying TOPSIS method in terms of measuring employees' job performance can conduct to measure qualitative works converting into quantitative works.

Bu çalışmanın amacı, entropy tabanlı TOPSİS yöntemi ile çalışanların iş davranışı performansının ölçülmesidir. Bu amaçla iş davranışlarından; tükenmişlik, duygusal emek, işten ayrılma niyeti ve iş tatmini ölçekleri değerlendirme kriteri kabul edilerek bir kamu üniversitesi çalışanlarına anket uygulanmıştır. Tüm kriterlerin bütünleşik olarak değerlendirilmesi performans ölçümü için hayati öneme sahiptir. Bu açıdan bakıldığında, çok kriterli karar verme yöntemleri uygun bir çatı sunmaktadır. Çok kriterli karar verme yöntemleri insan kaynakları alanında performans değerlemede kullanılmaktadır. Performans değerlemeyi sadece yapılan iş sayısına göre değil, işletmeye karşı, işe karşı, hizmet verilen kişilere karşı tutumlara göre ölçmek amacıyla bu yöntem kullanılmıştır. TOPSİS yöntemi ile yapılan çalışmaların az olduğu dikkate alınırsa, literatüre katkı sağlayacağı düşünülmektedir. Ölçeklerdeki en uygun durumlar, zıt yönlü olduğu için bu ölçekleri bir tek değere indirgemek için çok kriterli karar verme yöntemlerinden biri olarak kabul edilen TOPSIS yöntemi uygulaması sonucunda, iş davranışları performans ölçümü konusunda, nitel çabaların nicel hale getirilerek ölçülmesi bağlamında katkı sağladığı düşünülmektedir.
Keywords: TOPSİS; Performans yönetimi; TOPSIS; Performance management